Urgensi Sertifikat Layak Kawin Dalam Hukum Perkawinan - Wahdaniah Baharuddin (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The course for prospective brides, which is then equated with Marriage Guidance, hereinafter referred to as bimwin, is a mandatory requirement that must be carried out by the prospective bride and groom before carrying out a wedding because the prospective bride and groom who have attended are given a certificate as proof of graduation which is a requirement for marriage registration. The certificate referred to before being used is given serial number/registration.Purposes of the Research: This study aims to determine the urgency of a certificate of eligibility to marry as a formal requirement in marriage law. Methods of the Research: This research is normative legal research. The approach is carried out by reviewing the literature or literature studies according to the problem under study.Results of the Research: This shows that the implementation of marriage guidance is a must for prospective husband and wife couples who want to get married. Every couple who wants to get married is required to attach a certificate of eligibility to marry that has been obtained after participating in the marriage guidance program. Prospective bride and groom must attach a certificate of eligibility to marry which has been given a serial/registration number. The obligation to attach a certificate as one of the administrative requirements for marriage registration has been regulated in statutory regulations, but because there are no strict sanctions against prospective brides who do not attend courses, the mandatory arrangement to attach a marriage certificate is a mere paper issue and provides an opportunity for the prospective bride and groom to not taking the course.